Genetic diversity evaluation of Luculia yunnanensis, a vulnerable species endemic to Yunnan, Southwestern China based on morphological traits and EST-SSR markers - Zhang, Yao; Wan, Youming; Qu, Suping; Mu, Zhengchun; Li, Yuying; Li, Zhenghong (Frontiers in Plant Science, 2024)
Luculia yunnanensis is a vulnerable species endemic to Yunnan Province, Southwestern China, which has high ornamental value. Its wild population has not been fully protected and utilized for a long time, which is not conducive to the long-term stable development of this species. Genetic diversity assessment is the basis and prerequisite for the conservation of rare species. In this study, 21 phenotypic traits and 17 highly polymorphic EST-SSR markers were used to analyze the genetic diversity and genetic structure of 164 individuals from six L. yunnanensis populations. The coefficient of variation of 21 phenotypic traits ranged from 11.76% to 52.58% (mean=21.72%), and the coefficient of variation of 18 traits was less than 30%. The average values of Ne, I, Ho and He were 1.710, 0.619, 0.384, and 0.352, respectively. The genetic diversity of LLO (Ho = 0.476 and He = 0.426) and LCM (Ho = 0.424 and He = 0.381) populations in Lushui County was highest. The GDX populations (Ho = 0.335 and He = 0.269) isolated by Gaoligong Mountain had the lowest genetic diversity. The AMOVA results showed that 13.04% of the genetic variation was among populations and 86.96% was within populations. The average phenotypic differentiation coefficient of phenotypic traits among populations was 18.69%. The results of phenotypic and genetic variation analysis were consistent, indicating that the most of variation exists within population. Genetic structure, UPGMA clustering and PCA analysis results showed that the populations of L. yunnanensis had obvious geographical divisions, and the populations distributed in the southern region and distributed in the northern region of the Nujiang River clustered into one group respectively. Combining the results of phenotypic and molecular markers, we recommend that give priority to the protection of LLO, LCM and GDX population, in order to ensure the sustainable utilization of L. yunnanensis germplasm resources.